Lipang, Langkuru, Waisika Language Kinship: Lexicostatistics Study in Alor Island - Anggayana, Wayan Agus (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the language kinship level by determining the pattern of relationships between languages depicted in the genealogy of kinship and finding the type of sound change. The focus of research on language relations in Alor regency is significant to do with sustainability knowing the genealogy of local language Austronesian or Non-Austronesian.Data is in the form of Swadesh vocabulary list. Collected using field scientific research methods direct elicitation, recording, and checking elicitation. Analyzing data was carried out by using the lexicostatistics technique using comparative historical linguistics theory. The results of the quantitative analysis with the lexicostatistics technique. The highest percentage is 68% between Lipang-Langkuru languages, Lipang-Waisika language by 55%, Langkuru-Waisika language 47%, those areas a family group of language and has a close relationship. Therefore languages are hypothesized to originate from the same ancestral language, namely ProtoLipang-Langkuru-Waisika (PLpLnWs).